2019
DOI: 10.4103/ajns.ajns_289_18
|View full text |Cite
|
Sign up to set email alerts
|

The role of decompressive craniectomy in traumatic brain injury: A systematic review and meta-analysis

Abstract: The objective is to evaluate the efficacy of early decompressive craniectomy (DC) versus standard medical management ± late DC in improving clinical outcome in patients with traumatic brain injury (TBI). Electronic databases and gray literature (unpublished articles) were searched under different MeSH terms from 1990 to present. Randomized control trials, case–control studies, and prospective cohort studies on DC in moderate and severe TBI. Clinical outcome measures included Glasgow Coma Outcome Scale (GCOS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 36 publications
(87 reference statements)
2
20
0
3
Order By: Relevance
“…Several meta-analyses on DC in TBI population and its effects on long-term outcome are available in literature [20,22,24,37,45,55,65,68,69]. All these studies demonstrated the efficacy of DC in controlling ICP, reducing mortality and hospital length-of-stay, with an increased rate of unfavorable outcome when compared with medical treatment.…”
Section: The Staircase Approachmentioning
confidence: 99%
“…Several meta-analyses on DC in TBI population and its effects on long-term outcome are available in literature [20,22,24,37,45,55,65,68,69]. All these studies demonstrated the efficacy of DC in controlling ICP, reducing mortality and hospital length-of-stay, with an increased rate of unfavorable outcome when compared with medical treatment.…”
Section: The Staircase Approachmentioning
confidence: 99%
“…Nine hundred seventy three citations were obtained, most of which were not specific to the topic or did not meet the inclusion criteria. Six publications were retrieved that met the pre-determined inclusion criteria (1722). We eliminated Sahuquillo (17) because it included only one study (23), which was included also in four of the other included reviews (18, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Four of the five studies included both RCTs and NRSs, and one (21) included only RCTs. Three of the five studies used only RCTs in their MAs (18, 20, 21), one included both RCTs and NRSs in the MA (22), and one did not conduct a MA (19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Выбор вида трепанации черепа основывается на субъективных факторах, таких как предпочтение и квалификация нейрохирурга, устоявшиеся привычки. В связи с этим увеличивается количество трепанаций черепа, выполненных неоправданно, повторных оперативных вмешательств и повышается риск осложнений [13][14][15][16][17][18].…”
Section: вступлениеunclassified